Neuropsychological assessment protocol in an ongoing randomized controlled trial on posterior subthalamic area vs. ventral intermediate nucleus deep brain stimulation for essential tremor - Triguero-Cueva, Lucía; Marín-Romero, Bartolomé; Madrid-Navarro, Carlos Javier; Pérez-Navarro, María José; Iáñez-Velasco, Benjamin; Mínguez-Castellanos, Adolfo; Katati, Majed Jouma; Escamilla-Sevilla, Francisco (Frontiers in Neurology, 2023)
Objective Patients with essential tremor (ET) may experience cognitive-affective impairment. Deep brain stimulation (DBS) of different targets, such as the ventral intermediate nucleus (VIM) of the thalamus or the posterior subthalamic area (PSA), has been shown to be beneficial for refractory ET. However, there is little evidence regarding the possible neuropsychological effects of PSA-DBS on patients with ET, and there are few studies comparing it with VIM-DBS in this population. In this study, we aim to present the evaluation protocol and neuropsychological battery as used in an ongoing trial of DBS for ET comparing the already mentioned targets. Methods As part of a randomized, double-blind, crossover clinical trial comparing the effectiveness and safety of PSA-DBS vs. VIM-DBS, 11 patients with refractory ET will undergo a multi-domain neuropsychological battery assessment. This will include a pre−/post-implantation assessment (3 months after the stimulation of each target and 6 months after an open stage of DBS on the most optimal target). Conclusion Evidence on the neuropsychological effects of DBS in patients with refractory ET is very scarce, particularly in lesser-explored targets such as PSA. This study could contribute significantly in this field, particularly on pre-procedure safety analysis for tailored patient/technique selection, and to complete the safety analysis of the procedure. Moreover, if proven useful, this proposed neuropsychological assessment protocol could be extensible to other surgical therapies for ET.